Reasoning in knowledge bases with external and internal uncertainties - Dieu, Phan Đinh; Que, Tran Dinh (Journal of Computer Science and Cybernetics, 2016)
The paper presents a method of logical reasoning in knowledge bases with uncertainty; such a knowledge base is given by a set of “knowledges” of  two  following forms: 1)   <S,I> where S is a sentence, and I Í[0,1] is an interval of the possible values for truth probability of S. 2)   <S1,I1> Ù  <S2,I2> Ù …Ù <Sn,In> ® <S,I>, where S1, S2,…, Sn, S are sentences, and  I1, I2,…, In, I are the corresponding intervals of their truth probabilities. Let B be a  such knowledge base, and S be a goal sentence. The  interval of truth probabilities of S derived from B can be found by the  proposed method.